KAJIAN STRATEGI BRANDING CLOTHING UNKL347 - Rudy Farid (Wimba : Jurnal Komunikasi Visual, 2017)
Nowadays the success of a product to penetrate the market its not determined only by physical excellence, functions, pricing and the distribution aspects of the product. Amidst of myriad similar products offered to the consumer, now the key to conquest the competition is also determined by the branding strategy; that is the strategy of implanting the brand into consumer's mind. Because whenever confronted by many options, consumer is inclined to choose the brand that they know, trust and prefer.Regarding the brand building or branding, in 1996 occurred an exceptional phenomenon in Bandung City: UNKL347 a local clothing company was acknowledged to have a solid brand and compete against reputable international and regional brands. This occurrence raised inquisitions about how UNKL347 achieved its branding and perception in consumer's mind.So in order to comprehend this occurrence, a qualitative and case study methodology is employed. Information is investigated through an in-depth interview to UNKL347's principals, a structured interview to some purposive sampling of consumers and by documents observation. The analytical process is using an interactive method so the data's compilation is structured, comprehensible and its interconnectedness is constructed.The result or conclusion is there are some key factors which determined UNKL347's branding strategy achievement: that UNKL347 is unintentionally implementing branding strategy which is unconventional and even contradictory with conventional branding strategy, nevertheless the brand is conceived by personal recommendations among its consumers. This findings are expected to become as reference for brand building strategy in similar case and for a specific consumers / prospects.